Case Report: A dual challenge: navigating cardiac leiomyosarcoma and benign pulmonary mass - Wu, Song; Chen, Qiulin; Yang, Yi; Liu, Jialiang; Li, Yuankun; Cheng, Shengjun; Wu, Yutian (Frontiers in Cardiovascular Medicine, 2025)
Leiomyosarcoma is frequently found in the retroperitoneum, mesentery, omentum, uterus, or subcutaneous tissue. However, primary cardiac leiomyosarcoma is rare and even more uncommon is its coexistence with a benign tumor. We report a case involving a 61-year-old female with a right ventricular outflow tract leiomyosarcoma in conjunction with a benign mass located in the main pulmonary artery. Echocardiography revealed a 2.5 × 2.2 cm isoechoic mass in the right ventricular outflow tract and a 3.8 × 1.8 cm irregular isoechoic mass in the main pulmonary artery. Computed tomography angiography (CTA) indicated a patchy filling defect in a similar location. Initially, pulmonary embolism was considered, however, the possibility of tumors could not be excluded. Given the high risk of mass embolization, we proceeded with emergency surgery. A large, irregular, solid mass was found attached to the wall of the main pulmonary artery, fortunately without involvement of the pulmonary valve. Exploration of the right ventricular outflow tract uncovered an additional solid, smooth, well-encapsulated mass. Immunohistochemical analysis of the right ventricular outflow tract mass confirmed the presence of tumor cells that were positive for Desmin and smooth muscle actin (SMA), while negative for S-100 and myoglobin, leading to a diagnosis of leiomyosarcoma. For the pulmonary mass, Immunohistochemistry revealed the proliferation of fibrous tissue, mucus degeneration, and calcification within the focal area. The imaging characteristics of cardiac leiomyosarcoma combined with benign pulmonary artery tumors may be misinterpreted as thrombosis, however, surgical resection remains a viable treatment option.